Pengaruh Penanganan Keluhan dan Kualitas Produk Terhadap Kepuasan Anggota Pembiayaan Murabahah Koperasi Pegawai Negeri Banuhampu Sungai Puar - Mela Azmardiah; Jon Kenedi (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2026)
Abstract This study aims to identify the extent to which complaint handling and product quality influence the satisfaction of murabahah financing members at the Banuhampu Sungai Puar Civil Servants Cooperative. The research background arises from member complaints regarding the cooperative’s policy of refusing to process refinancing requests for murabahah financing. Such refusal reflects compliance with DSN Fatwa No. 89/DSN-MUI/XII/2013 on Islamic refinancing, which does not permit murabahah refinancing through the same contract. The study employs a quantitative correlational approach by distributing online questionnaires to 42 murabahah financing members. Sampling uses a saturated sampling, while data analysis is conducted with SPSS Version 26. The findings reveal: (1) Complaint handling (X1) has a positive but insignificant partial effect on member satisfaction (Y), with a value of 0.176 < 2.022 and significance level of 0.861 > 0.05. (2) Product quality (X2) has a positive and significant partial effect on satisfaction (Y), with a value of 10.359 > 2.022 and significance level of 0.000 < 0.05. (3) Complaint handling (X1) and product quality (X2) simultaneously exert a positive and significant effect on satisfaction (Y), with a value of 96.897 > 3.24 and significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.832, indicating that 83.2% of murabahah member satisfaction can be explained by complaint handling and product quality, while the remaining 16.8% is influenced by other variables outside this regression model. Keyword: Customer Satisfaction, Complaint Handilng, Murabahah Financing, Quality of Product.